Point-of-Care Tests for Bladder Cancer: The Influencing Role of Hematuria - Joerg Hennenlotter; Severine Huber; Tilman Todenhöfer; Ursula Kuehs; David Schilling; Stefan Aufderklamm; Georgios Gakis; Christian Schwentner; Arnulf Stenzl (Advances in Urology)
Introduction. Several point-of-care tests (POCT) are available for the diagnosis of bladder cancer (BC). We evaluate the impact of HU (hematuria) on performance of POCTs. Materials and Methods. Urine from 10 donors was diluted with blood from 0.5 to 0.00625%. BladderCheckR, BTAstatR, BCMR, and BTAR tests were applied. Tests were additionally conducted in 54 patients with HU. HU was stratified according to the amount of erythrocytes (RBC)/μL using two systems: (1) no HU; mild microscopic HU; severe microscopic HU; gross HU; (2) I <25 RBCs; <250 II; ≥250 III. Results were compared to HU status and histopathology. Results. Gross HU became evident between 2090 RBCs/μL and 1065/μL. Addition of blood led to default tests in all 4: BladderCheckR 0.25%; BCM 0.025%, BioNexia 0.00625%, and BTAstat <0.00625%. Rates of false positives for BladderCheck, BTAstat, BCM, and BioNexia were 5.9, 11.8, 0, and 1.8% without HU and 0, 66.7, 44.4, and 66.7% with HU. BTAstat, BCM, and BioNexia were independently influenced by HU (P<0.0002). Conclusions. NMP22-BladderCheck was most resistant to blood. The diagnostic yield of all others was significantly influenced by HU. A well-defined HU grading helps to define limits of HU for a reliable interpretation of BC-POCTs.